O programa federal brasileiro 'Minha casa, minha vida' é um regulador-sombra das normas urbanísticas municipais? - Acosta, Claudia (2015)
The program for social housing 'Minha Casa, Minha Vida' (PMCMV) is the largest public intervention on this subject in Brazil. This market-oriented initiative, which started in 2009, funded in six years around four million units. The program is implemented at the local level. The main objective of this dissertation is to understand whether this program leads to changes in urban regulation and, if so, how this is conducted. The monopoly power in the funding scheme – a merit common good that is typically undersupplied –, can change the municipal norms defining the regulatory agenda in order to attend the requirements of the program. The findings in this research corroborate that, given the federal resource incentive, the PMCMV works as a shadow regulator for urban regulation. As a matter of fact, municipal authorities change the urban legislation as a result of the program, but this is not homogeneous in the country nor has the same level of commitment by the municipality or in the process of democratic management of the territory. The analyzed cases show that the normative change cannot be regarded solely as an imposition from the federal government over the local government. The possibility of changing the norms is a tool for small and peripheral municipalities to compete for such resources.